Analisis Permohonan Pailit Terhadap Anak Perusahaan Perusahaan Umum (PERUM) yang Memiliki Diversifikasi Usaha Dihubungkan dengan Asas Kepastian Hukum dalam Kepailitan BUMN Holding - Audrey Ivana; Shelly Kurniawan (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Indonesia has several State-Owned Enterprises (SOEs) that implement diversification through a concentric scheme. As a result, there are several SOE Holding Companies whose subsidiaries operate in the same business sectors as the parent company. SOE Holding Companies are not exempt from the risk of bankruptcy, whether involving the parent company or the subsidiaries. Currently, Indonesia does not have regulations regarding the establishment of SOE Holding Companies and the bankruptcy of their subsidiaries. This research aims to examine the regulations surrounding SOE Holding Companies and the responsibility of SOE Holding Companies in the form of a Public Corporation (Perum) for their subsidiaries that experience bankruptcy. This study uses a normative juridical approach, with legislative and conceptual perspectives, to discuss the regulations on bankrupting SOE subsidiaries in the form of a Public Corporation. The research object is the subsidiaries of SOEs. The findings of this study show that, first, the parent company and the subsidiary are separate and independent legal entities based on the principles of separate legal entity and limited liability. Second, the bankruptcy of a subsidiary will only affect the loss of capital and the decline in the wealth of the SOE Holding. The SOE Holding Company cannot be directly held liable for the subsidiary’s debts, but it may be held accountable if it is proven that its decisions caused the subsidiary’s bankruptcy.